Fluorine important element in new drugs synthesis: Review Study - Ahmed Mahmood; Mohammed Al-Iraqi; Faris Abachi (University of Mosul, 2018)
Objective:To evaluate the role of fluorine atom in modern drug synthesis. Methods:  Different types of fluorinated were prepared, antimicrobials, antivirals, F-NSAIDs, peptides and protein synthesis. Results: Recent developments and future prospects of fluorine in medicinal chemistry and chemical biology. The extraordinary potential of fluorine - containing biologically relevant molecules in antimicrobial or antivirial agents, or  peptide or protein chemistry, medicinal chemistry, chemical biology, pharmacology, and drug discovery as well as diagnostic and therapeutic applications, was recognized by researchers who are not in the traditional fluorine chemistry field, and thus the new wave of fluorine chemistry has been rapidly expanding its biomedical frontiers. Conclusion: This review how to list of fluorinated drugs( Antimicrobial agents , anticancer agents, Antiviral agents, and study their  physicochemical properties of fluorine drugs.